2011
DOI: 10.1007/s11814-010-0533-8
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic extraction using two phase laminar flow for chemical and biological applications

Abstract: We review the state of the art in microfluidic separation technique based two-phase laminar flow with an application focus on chemical and biological sample. As we describe herein, two-phase laminar flow in the microfluidic extraction has several biological and engineering advantages over other methods including high reproducibility, biocompatibility, and selectivity. We review advances in applications of two-phase laminar flow and examine key parameters such as flow rate, phase composition, and surface charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…미세유체 시스템(microfluidic system)은 시약의 소모량이 적고 반 응 시간의 단축이 용이하며 높은 감도(sensitivity)를 갖는 특성으로 인하여 생 화학적 분야의 연구에 널리 사용되고 있다 [1][2][3][4][5]. 그 중 액 적 기반의 미세유체 시스템은 서로 섞이지 않는 두 유체를 이용하여 단순한 액적을 형성시키는 기술로써, 생성된 액적은 내부에 특정 물 질을 함입(encapsulation)시켜 작은 반응기 또는 운반체로써 사용될 수 있다 [6][7][8].…”
Section: 서 론unclassified
“…미세유체 시스템(microfluidic system)은 시약의 소모량이 적고 반 응 시간의 단축이 용이하며 높은 감도(sensitivity)를 갖는 특성으로 인하여 생 화학적 분야의 연구에 널리 사용되고 있다 [1][2][3][4][5]. 그 중 액 적 기반의 미세유체 시스템은 서로 섞이지 않는 두 유체를 이용하여 단순한 액적을 형성시키는 기술로써, 생성된 액적은 내부에 특정 물 질을 함입(encapsulation)시켜 작은 반응기 또는 운반체로써 사용될 수 있다 [6][7][8].…”
Section: 서 론unclassified
“…An important advancement related to the integrative microfluidic extraction has been also investigated by combining an electric field and two-phase laminar flow. These types of extractions, coupled with external force, electric or magnetic, and affinity agents, will certainly play an even more important role in the next generation methods of microfluidic extraction-based two-phase laminar flow systems (78,79).…”
Section: New Techniques Integrated With Atpssmentioning
confidence: 99%
“…The use of ATPS in microfluidic platforms is fairly recent and still in the research phase [1], but several reports have shown the application of microfluidic ATPS in separating whole cells [8], tagged proteins [9], monoclonal antibodies [10], among others biomolecules [1]. Microfluidics is particularly attractive due to the possibility of creating a parallel laminar flow of the phases with the interface running along the microchannel due to the laminar flow; the very large surface area-to-volume ratio [11]; and the easy separation of the phases [1], leading to the possibility of continuous processing and to a possible increase of the separation efficiency and speed [1,11].…”
Section: Introductionmentioning
confidence: 99%